Global Dynamics of a Filippov-Type Predator-Prey System with the Prey Refuge - YANG Miao;HUANG Lihong;WANG Jiafu;HUANG Chuangxia (Nantong Daxue xuebao. Ziran kexue ban)
Based on the classical predator-prey model, a class of Filippov predator-prey model with prey refuge is studied on account of the prey refuge and the proportional control threshold strategy. The local and global dynamics of this model are qualitatively analyzed by using the theory of the differential equation with the discontinuous right-hand side.Under certain parameter conditions, the correlation results of the global asymptotic stability of the model are obtained.